Skoulekia erythrini n. sp. (Digenea: Aporocotylidae): a parasite of Pagellus erythrinus (L.) (Perciformes: Sparidae) from the western Mediterranean with an amendment of the generic diagnosis - Palacios-Abella, José F; Georgieva, Simona; Mele, Salvatore; Raga, Juan Antonio; Isbert, Wolf; Kostadinova, Aneta; Montero, Francisco E (Systematic parasitology, 2017)
A new aporocotylid, Skoulekia erythrini n. sp., is described from the heart, cephalic kidney and gill blood vessels of the common pandora Pagellus erythrinus (L.) collected from several localities of the western Mediterranean off Spain. The new species differs from the type- and only species of the genus, S. meningialis Alama-Bermejo, Montero, Raga & Holzer, 2011 in possessing a symmetrical body (vs laterally curved), short tegumental spines (3-4 vs 7-10 µm) without hooked ends, diffuse (vs conspicuous) oesophageal gland-cells, a relatively longer oesophagus, a testis that is shorter in relation to body length and a much smaller seminal vesicle (17-34 × 10-26 vs 33-101 × 27-97 μm). Elongated ellipsoidal eggs of S. erythrini n. sp. were found trapped in gill vessels in histological sections. Phylogenetic analyses based on partial 28S rDNA and ITS2 sequences supported the placement of the new species within Skoulekia and the close relationships of this genus with Psettarium Goto & Ozaki, 1929 and Pearsonellum Overstreet & Køie, 1986. Skoulekia meningialis is described from a new sparid host, Diplodus puntazzo (Walbaum), collected off Santa Pola, Spain. The new morphological data for the two Skoulekia spp. and a re-examination of three paratypes of S. meningialis pinpointed features amending both the description of S. meningialis and the generic diagnosis of Skoulekia.
Keywords: Perciformes; mezerníky ribozomální DNA; druhová specificita; Animals; RNA ribozomální 28S; Trematoda; Mediterranean Sea; DNA, Ribosomal Spacer; Středozemní moře; zvířata; RNA, Ribosomal, 28S; Species Specificity